Heterogeneity of outcomes for intraoperative music interventions: a scoping review and evidence map. Issue 3 (19th August 2020) - Ambler, Melanie; Springs, Stacey; Garcia, Dioscaris; Born, Christopher
Abstract : Background: Over the past 30 years, numerous studies have been performed that assess the efficacy of intraoperative music as an adjunctive means to regional and local anaesthesia to improve clinical outcomes. Despite an emerging body of evidence and growing adoption of music in surgical settings, the variety of interventions studied, and the heterogeneity of outcomes and outcome measurement tools applied makes difficult the task of aggregating evidence. Objective: This study assesses the state of the field of intraoperative musical interventions by documenting and visualising the breadth of outcomes measured in studies. Design: Scoping review and evidence map. Methods: Three electronic databases (PubMed, Embase and a music-focussed research database, RILM (International Music Literature Repository)) were searched for full-text articles published between January 1991 and July 2019. Results from these searches were screened and relevant data was extracted from full-text articles on type of music intervention and type of anaesthesia; outcomes measured were recorded in an evidence map in order to identify the current state of the field and assess for trends in outcome measurements. Interventions: Music administered to adult patients via headphones or speakers under regional or local sedation in during the intraoperative period. Results: Twenty-one studies with a total of 2283 patients were included. A total of 42 unique outcomes were measured across the 21 studies, with each measuring an average of 6.41±2.63 outcomes. Systolic blood pressure, diastolic blood pressure, heart rate, anxiety, pain, patient satisfaction, respiratory rate and sedation requirements were the most prevalent outcomes reported. Only 15 outcome measures (36%) were used in more than one study, while the remaining 27 outcome measures (64%) were identified in only one study in our review. Conclusions: Our scoping review identifies that almost two-thirds of studies in this field used > 1 outcome measure unique to that study (not also used in other studies), which hinders opportunities to aggregate data across studies and meta-analyse evidence. Future studies should provide clear documentation regarding the intervention and consider using valid and reliable outcome tools. Researchers should consider standardisation when appropriate and adopting the use of core outcome sets for conditions where these sets have been developed.